2019
DOI: 10.1155/2019/2514312
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Estrogens in Thyroid Redox Homeostasis and Carcinogenesis

Abstract: Reactive oxygen species (ROS) are the most critical class of free radicals or reactive metabolites produced by all living organisms. ROS regulate several cellular functions through redox-dependent mechanisms, including proliferation, differentiation, hormone synthesis, and stress defense response. However, ROS overproduction or lack of appropriate detoxification is harmful to cells and can be linked to the development of several diseases, such as cancer. Oxidative damage in cellular components, especially in D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 147 publications
(146 reference statements)
1
19
0
5
Order By: Relevance
“…Estrogen acts increasing iodide uptake, TPO activity and TG expression, and it modulates TSH level. Furthermore, estrogen also influences the thyroid gland redox status, as previously reported 17,33 . It is conceivable that the mechanisms underlying this influence involve the estrogen-regulated NOX4 and DUOX2 activity and expression.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Estrogen acts increasing iodide uptake, TPO activity and TG expression, and it modulates TSH level. Furthermore, estrogen also influences the thyroid gland redox status, as previously reported 17,33 . It is conceivable that the mechanisms underlying this influence involve the estrogen-regulated NOX4 and DUOX2 activity and expression.…”
Section: Discussionsupporting
confidence: 56%
“…Even though studies have demonstrated a relationship between thyroid pathologies and thyrocytes redox imbalance 15 17 , the interconnection between metabolic programming and oxidative stress in the thyroid is mostly unknown. Our hypothesis is that maternal exposure to nicotine during breastfeeding impact directly the redox homeostasis of the thyroid gland, impairing the thyroid hormonogenesis process in the offspring and imprinting thyroid dysfunctions later in life.…”
Section: Introductionmentioning
confidence: 99%
“…Because high levels of ROS are produced during thyroid hormone synthesis, mitochondrial defense mechanisms against ROS are important in thyroid follicular cells. These antioxidant defense systems have been found to be inactive in thyroid cancers 4 , 5 . In Hürthle cell carcinoma, a rare type of differentiated thyroid cancer is characterized by excess mitochondria as well as defective mitochondrial oxidative phosphorylation 6 .…”
Section: Introductionmentioning
confidence: 99%
“…E 2 can inactivate vascular smooth muscle inflammatory NFκB and TNFα signaling and promote flow-mediated vasodilation [ 3 , 4 , 10 , 11 ], but E 2 stimulation of blood flow can also paradoxically increase vascular oxidative stress through dramatic effects on cellular metabolism [ [12] , [13] , [14] ]. Therefore, we tested whether E 2 perturbs crucial elements of redox homeostasis in WT and CSE KO uterine and renal arteries.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its vasodilatory role, E 2 influences redox homeostasis. E 2 attenuates pro-oxidant NFκB and TNFα pathways [ 10 , 11 ], but paradoxically increases superoxide (O 2 − ) and hydrogen peroxide (H 2 O 2 ) production [ 12 , 13 ]. In some situations, E 2 replacement therapy can exacerbate post-menopausal cardiovascular disease [ 14 ].…”
Section: Introductionmentioning
confidence: 99%